Associations between overweight, health behaviors and Figure Rating Scale by Stunkard at 18-year-old secondary school students from Wroclaw - Więckowska, Karolina; Wrzosek, Zdzisława; Kuciel, Natalia; Dadacz, Joanna; Lwow, Felicja (Journal of Education, Health and Sport, 2019)
Introduction: Overweight in adolescence are associated with unfavourable consequences throughout the life-span, especially in chronic disorders such metabolic syndrome, type 2 diabetes.. Diet, physical activity and psychosocial factors are important risk factors of obesity in this group. The aim of the study was to find the relationship between the body mass index (BMI) and diet, physical activity and perception of body mass according to Figure Rating Scale by Stunkard. Material and methods: The study involved 104 secondary school students from Wrocław aged 18 years old (84 girls and 20 boys). Physical activity was assessed by the International Physical Activity Questionnaire (IPAQ) (http://www.ipaq.ki.se). Original survey questionnaire, based on the health programme “Keep straight”, was used to assess selected behaviors in the field of nutrition. Perception of body mass was checked with the Figure Rating Scale, according to Stunkard. The anthropometric research was based on the body weight, height, waist and hip circumference, BMI and WHR were calculated. Results: Most of the students (82%) represented a proper BMI, respectively 83% girls and 75% boys and correctly percepted their body mass index. We have shown adverse relationship between BMI and the number of dietary errors (r=-0,23, p<0,05) Only the nutrition model had a statistically significant effect on the BMI value within the studied group (OR=2,990, p< 0,05). Conclusions: Most secondary students of the metropolitan area represented the recommended level of physical activity and preferred the correct model of nutrition regardless of gender. There is a relationship between the nutrition model, body mass perception and the BMI in the group of 18 years old secondary school students. Research should be continued on a larger group.